Development of Module in Filipino sa Piling Larang (Technical Vocational -Carpentry Strand) - Quidato, Julie Gay B.; Federizo, Clarice (Future Science / FSH-PH Publications, 2023)
This study focus on the development of the Piling Larang (Tech-Voc Carpentry Strand) module. The problems face by teachers are the main basis for developing this module. This study adopted a developmental design and the ADDIE paradigm. At this point, the researcher surveyed the instructors who teach Filipino in Piling Larang (Tech Voc) to find out what the most frequent issues are with teaching Filipino in Piling Larang Tech-Voc. The survey's findings served as the researcher's foundation for creating the module. In response to the results of the analysis of the findings of the survey among the teachers, the researcher designed the module for the Filipino subject in Piling Larang in Grade 12 (Tech-Voc Carpentry). Based on the competencies established by the Filipino curriculum guide, each lesson's goals are set. The researcher creates assignments for each session that correspond to the abilities the students need to learn, and the module's content is drawn from many basic texts. Each assignment is centered on the Carpentry strand, the course that students attend to advance their knowledge in that area. A group of validator assessed the generated module and offered the necessary adjustments and corrections. Based on the validator’s comments and suggestions, the researcher revised and improved the module.